Glycaemic control and hypoglycaemia risk with insulin glargine 300 U/mL and insulin degludec 100 U/mL in older participants in the BRIGHT trial. Issue 7 (1st April 2021) - Bolli, Geremia B.; Cheng, Alice; Charbonnel, Bernard; Aroda, Vanita R.; Westerbacka, Jukka; Bosnyak, Zsolt; Boëlle‐Le Corfec, Emmanuelle; Rosenstock, Julio
Abstract: Aim: To evaluate the efficacy and safety of insulin glargine 300 U/mL (Gla‐300) versus insulin degludec 100 U/mL (IDeg‐100) in predefined (</≥65 years) and post hoc (</≥70 years) age groups of people with type 2 diabetes (T2D) in the BRIGHT trial. Materials and Methods: BRIGHT was the first head‐to‐head randomized trial comparing Gla‐300 and Deg‐100 in insulin‐naïve adults with T2D. In this subanalysis, endpoints were studied by predefined (</≥65 years, N = 596/333) and post hoc (</≥70 years, N = 768/161) age groups. Results: Heterogeneity of treatment effect was observed for HbA1c reductions across the </≥70 years subgroups, but not across the </≥ 65 years subgroups, with greater HbA1c reductions with Gla‐300 versus IDeg‐100 in those 70 years or older (least squares mean −0.34% [95% confidence interval: −0.589% to −0.100%]). There was no significant heterogeneity of treatment effect for incidence and rates of confirmed (≤3.9 mmol/L [≤70 mg/dL]) hypoglycaemia across any age subgroups over 24 weeks, but numerically lower incidence and rates were consistently observed for Gla‐300 versus IDeg‐100 in the 65 years or older and 70 years or older age groups in the initial 12 weeks. Conclusions: Gla‐300 may be a suitable treatment option in the growing population of older people with T2D. Further investigation is required to determine Gla‐300 glycaemic benefits in high‐risk populations without increasing the risk of hypoglycaemia.